2015
DOI: 10.15537/smj.2015.2.10267
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene insertion/deletion polymorphism in Saudi patients with rheumatic heart disease

Abstract: Objectives:To investigate the association between angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism and rheumatic heart disease (RHD) in Saudi patients.Methods:A case-control study was conducted in Saudi RHD patients. Genomic DNA was isolated from 99 RHD patients attending the Pediatric Cardiology Clinic at the Maternity and Children Hospital, Al-Madinah, Saudi Arabia from March 2013 to June 2014, and from 145 age- and gender-matched controls. Patient clinical records were reviewed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Moreover, it could be helpful for optimizing prevention and intervention strategies at population levels, as reported in Ruggenenti et al (2008) [23], also its reported that characterization of the ACEI/D gene polymorphism has been suggested for decision making in relation to antihypertensive treatment regimens [24]. In regard to the association of ACE genotypes with CVD or heart thrombosis, it was not statistically significant, and this is in concordance with Saqer et al (2016) [12] , but not with a study conducted in Saudi Arabia study [25], which found an increased CVD risk with ACE I/D polymorphism. The relationship between ACE genotypes and retinopathy was also not statistically significant, and this is similar to another study conducted in Iran [26].…”
Section: Abuaisha Et Alsupporting
confidence: 71%
“…Moreover, it could be helpful for optimizing prevention and intervention strategies at population levels, as reported in Ruggenenti et al (2008) [23], also its reported that characterization of the ACEI/D gene polymorphism has been suggested for decision making in relation to antihypertensive treatment regimens [24]. In regard to the association of ACE genotypes with CVD or heart thrombosis, it was not statistically significant, and this is in concordance with Saqer et al (2016) [12] , but not with a study conducted in Saudi Arabia study [25], which found an increased CVD risk with ACE I/D polymorphism. The relationship between ACE genotypes and retinopathy was also not statistically significant, and this is similar to another study conducted in Iran [26].…”
Section: Abuaisha Et Alsupporting
confidence: 71%
“…A meta-analysis of twin studies estimated that 60% of RF risk was heritable ( 12 ), which is higher than some other well-characterized complex autoimmune diseases ( 13 ). These data highlight the importance of a genetic component to the disease, and genetic variability in inflammatory and immune genes has been associated with RHD development and severity ( 10 , 14 16 ).…”
Section: Introductionmentioning
confidence: 78%
“…In the present study on 418 patients from western Black Sea region of Turkey, however, ACE gene I/D polymorphism and ACE gene alleles were not found to be associated with liver fibrosis severity. The ACE gene DD genotype is thought to be associated with an increased risk of rheumatic heart disease in the Saudi population (Al-Harbi et al, 2015), with nitric oxide metabolite levels and systolic blood pressure in clinically healthy Mexican men (no effect in women) (Avila-Vanzzini et al, 2015), with high altitude pulmonary edema in an Indian population (Bhagi et al, 2015), with sepsis susceptibility in Chinese patients (Yang and Zhou, 2015), with periodontal disease susceptibility in a Korean population (Kang et al, 2015), and with cancer risk in Caucasians (Zhang et al, 2014). It has been suggested that ACE gene I/D polymorphism is a genetic risk factor for Alzheimer's disease in a Chinese population (Yuan et al, 2015), while there is reportedly no association between ACE I/D gene polymorphism and a number of conditions and associated risks including type 1 diabetic nephropathy (T1DN) susceptibility and the risk of patients with type 1 diabetes mellitus developing T1DN in a Caucasian population , chronic obstructive pulmonary disease (Ayada et al, 2014) and retinal vein occlusion (Kutlutürk et al, 2014) in a Turkish population, as well as type 2 diabetic nephropathy (T2DN) susceptibility and the risk of patients with type 2 diabetes mellitus developing T2DN in Caucasian populations .…”
Section: Discussionmentioning
confidence: 99%